Sensor, Signal, and Imaging Informatics - Hsu, W.; Park, S.; Kahn, Charles E., Jr.; Section Editors for the IMIA Yearbook Section on Sensor, Signal, and Imaging Informatics (Yearbook of Medical Informatics, 2017)
Objective: To summarize significant contributions to sensor, signal, and imaging informatics published in 2016.Methods: We conducted an extensive search using PubMed® and Web of Science® to identify the scientific contributions published in 2016 that addressed sensors, signals, and imaging in medical informatics. The three section editors selected 15 candidate best papers by consensus. Each candidate article was reviewed by the section editors and at least two other external reviewers. The final selection of the six best papers was conducted by the editorial board of the Yearbook.Results: The selected papers of 2016 demonstrate the important scientific advances in management and analysis of sensor, signal, and imaging information.Conclusion: The growing volume of signal and imaging data provides exciting new challenges and opportunities for research in medical informatics. Evolving technologies provide faster and more effective approaches for pattern recognition and diagnostic evaluation. The papers selected here offer a small glimpse of the high-quality scientific work published in 2016 in the domain of sensor, signal, and imaging informatics.
Keywords: Signal processing; biomedical imaging; deep learning; computer aided diagnosis; data integration